Waiting for "Superman" : how we can save America's failing public schools - Weber, Karl. (New York : PublicAffairs, 2010)
This book explores politically charged topics through a series of essays by thinkers at the leading edge of educational innovation. It shows how failing schools destroy neighborhoods--not the reverse--and how research reveals that dedicated, attentive teachers are what help at-risk kids succeed. Inspired the film directed by "An Inconvenient Truth"'s Davis Guggenheim.
Prologue: The problem. A nation still at risk -- pt. 1: The film. Introduction: waiting for "Superman"-the story behind the movie -- Voices from waiting for "Superman" -- The making of waiting for "Superman" / Davis Guggenheim -- The road to super Tuesday / Lesley Chilcott -- pt. 2: Francisco. Introduction: Francisco's story -- How school kill neighborhoods-and can help save them / Bill Strickland -- The difference is great teachers / Eric Hanushek -- g pt. 3: Emily. Introduction: Emily's story -- Calling all citizens / Eric Schwarz -- pt. 4: Anthony. Introduction: Anthony's story -- Putting kids first / Michelle Rhee -- Five foundations for student success / Randi Weingarten -- pt. 5: Bianca. Introduction: Bianca's story -- What really makes a super school? / Jay Mathews -- pt. 6: Daisy. Introduction: Daisy's story -- Bringing change to scale: the next big reform challenge / Geoffrey Canada -- Educating America's young people for the global economy / Melinda Gates -- pt. 7: What you can do. How you can make a difference / The Alliance for Excellent Education -- Web sites and organizations devoted to children, schools, and education reform -- Mom Congress lesson plan for change editors of Parenting magazine.
Includes bibliographical references (p. 265-269) and index.
Keywords: Educational accountability -- Law and legislation -- United States; Education -- Standards -- United States; Education -- United States -- Evaluation; School improvement programs -- United States; Educational equalization -- United States